2015
DOI: 10.1177/1359105315573436
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the motives and mental health correlates of intentional food restriction prior to alcohol use in university students

Abstract: This study explored the prevalence of and motivations behind 'drunkorexia' – restricting food intake prior to drinking alcohol. For both male and female university students (N = 3409), intentionally changing eating behaviour prior to drinking alcohol was common practice (46%). Analyses performed on a targeted sample of women (n = 226) revealed that food restriction prior to alcohol use was associated with greater symptomology than eating more food. Those who restrict eating prior to drinking to avoid weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 25 publications
4
35
1
Order By: Relevance
“…Other studies have reported upwards of 46-58% of college students engage in these behaviors at least "sometimes" (Knight, Castelnuovo, Pietrabissa, Manzoni, & Simpson, 2016;Roosen & Mills, 2015). Importantly, caloric compensation may occur before, during, or after alcohol consumption (Rahal et al, 2012).…”
Section: Food and Alcohol Disturbance : A Brief Overviewmentioning
confidence: 97%
See 3 more Smart Citations
“…Other studies have reported upwards of 46-58% of college students engage in these behaviors at least "sometimes" (Knight, Castelnuovo, Pietrabissa, Manzoni, & Simpson, 2016;Roosen & Mills, 2015). Importantly, caloric compensation may occur before, during, or after alcohol consumption (Rahal et al, 2012).…”
Section: Food and Alcohol Disturbance : A Brief Overviewmentioning
confidence: 97%
“…were more likely to be willing to eat or even to increase food intake prior to drinking in an effort to prevent a hangover compared to women (Roosen & Mills, 2015). Thus, while both men and women report engaging in FAD behaviors, the functions of these behaviors may vary by gender.…”
Section: Food and Alcohol Disturbance : A Brief Overviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Roosen and Mills () found that 46% of university students intentionally changed eating behaviors before drinking alcohol. Limiting caloric intake prior to drinking puts college students at an increased risk for becoming intoxicated and subsequently experiencing negative alcohol‐related consequences; female students who engage in this behavior are likely to report memory loss, injury, having unprotected sex, and being taken advantage of sexually, while men are likely to engage in physical fights (Giles, Champion, Sutfin, McCoy, & Wagoner, ).…”
mentioning
confidence: 99%